Nilai Pendidikan Pranikah Dalam Al-Qur'an Surat Al-Hujurat Ayat 13 (Kajian Ilmu Pendidikan Islam) - Raito, Raito; Ramadan, Muhamad Fajar (STAI Al-Musaddadiyah Garut, 2023)
The Qur'an serves as a guide in human life, offering direction on various issues faced by humanity, including pre-marital considerations. Pre-marriage, or pranikah, is the initial step towards fulfilling the objectives of marriage. The Qur'an contains numerous verses that address pre-marital education, notably in Surah Al-Hujurat, Ayah 13. This particular verse encompasses several values pertinent to pre-marital education. This research aims to describe the pre-marital educational values contained in Surah Al-Hujurat, Ayah 13, from the perspective of Islamic Educational Science. This study adopts a library research methodology, involving an analysis of the interpretations provided by Islamic scholars (mufassir) on Surah Al-Hujurat, Ayah 13, and the educational pre-marital values as articulated by experts and religious scholars. The research utilizes a qualitative approach, focusing on content analysis of Surah Al-Hujurat, Ayah 13, and relevant texts. The findings suggest that the values embedded in Surah Al-Hujurat, Ayah 13, are associated with Akidah Education (Tarbiyatul Aqidah/Imaniyah), Shari'ah Education (Tarbiyatul Ibadah), and Akhlaq Education (Tarbiyatul Akhlaq). The pre-marital educational values derived from Surah Al-Hujurat, Ayah 13, in the context of Islamic Educational Science, emphasize the importance of faith in Allah SWT, who created mankind as male and female, and diversified them into various ethnicities and nations. This diversity necessitates mutual acquaintance or ta'aruf before entering marriage. By fostering trust and mutual understanding, individuals are encouraged to develop piety and devotion to Allah SWT. Keywords : Pre-marital Education, Qur'anic Interpretation, Islamic Educational Values